A Comparative Study of Participation in Extracurricular Activities between Children with and without Attention-Deficit/Hyperactivity Disorder: A comparative study of participation in extracurricular activities - Malek, Mohammad Sadegh; Askary Kachoosany, Reihaneh; pashazadehazari, Zahra (Iranian Journal of Child Neurology, 2025)
Objectives: The symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD) consist of persistent challenges with lack of attention and/or hyperactivity and impulsiveness. ADHD can have far-reaching and long-lasting effects on every part of an individual’s life, influencing various areas such as daily activities, work, social participation, and family life. “Engagement in a life situation” defines participation and encompasses various aspects, including being present and actively engaging. There is increasing evidence that children diagnosed with ADHD have restricted participation compared to their typically developing peers. Little research has focused on the involvement of children with ADHD in their everyday routines and leisure activities. Hence, this study aims to investigate the participation patterns in extracurricular activities among children with and without ADHD. Materials & Methods: The participants included 100 children aged 7-11 years with ADHD and 100 children without ADHD of the same age. They were recruited from multiple clinics and one hospital across Tehran city as a convenient sample. All the participants completed the child symptom inventory (CSI-4) and the Children’s Assessment of Participation and Enjoyment (CAPE). The study examined various aspects of participation, including diversity, intensity, enjoyment, place, and partners across 55 activities. The study was conducted online and completed by parents. Results: the two groups showed no statistically significant difference in demographic characteristics (P> 0.05). The results show that children with ADHD had notably lower participation rates in all types and domains of activities, indicating lower intensity (P value<0.001). Conclusion: Based on this study’s findings, children between the ages of 7 and 11 with ADHD experience significant limitations in engaging in daily activities compared to their typical peers. According to the results, including extracurricular activities in treatment plans seems particularly significant. Therapists and parents should focus on the child’s daily life at home and in therapy sessions and emphasize the inclusion of extracurricular activities in the treatment of children with AD